Seed germination in Solidago ×niederederi (Asteraceae) and its parental species after two different fruit storage periods - Pliszko, Artur; Kostrakiewicz-Gierałt, Kinga (Biodiversity: Research and Conservation, 2017)
In this paper, we present preliminary results from the study on the effect of fruit storage period on seed germination in Solidago ×niederederi and its parental species (S. canadensis and S. virgaurea). We aimed to test the hypothesis that a long fruit storage period (i) reduces the final percentage and speed of seed germination, as well as (ii) increases the number of dead seeds among non-germinated ones. We used fruit samples collected in Kraków, southern Poland, in 2013 and 2016, designating two different fruit storage periods of 3.5 years and 0.5 years, under dry, room temperature conditions. Seeds of all the observed species presented remarkably higher final percentage of germination after the short storage period than after the long one. The seeds subjected to the short fruit storage period achieved significantly higher values of Timson’s index and coefficient of velocity, as well as significantly lower values of the mean germination time than samples subjected to the long fruit storage period. After the long storage period, a significantly higher number of dead seeds among non-germinated seeds was found in S. ×niederederi and S. virgaurea. The performed studies showing that the long fruit storage period led to low contribution of germinated seeds in S. ×niederederi and its parental species suggested that the longtime seed desiccation had a negative impact on final germination. Considering that the hybrid can be potentially cultivated for scientific, medicinal or ornamental purposes, the suggested fruit storage period, under dry, room temperature conditions, should be shorter than three years. However, we realize that the response to long storage may vary in different populations and, therefore, further investigations are needed.